Quest for a better operation system in education: Privatization and teacher educationalization or voucherilization glimpsing from consumer and product perspectives - Alam, Gazi Mahabubul; Hoque, Kazi Enamul; Oke, O.K. (Academic Journals, 2010)
Inevitably, education is considered as the main tool for development. Regardless of nationality, race, age and culture, everyone in this contemporary world believes that education is the commonest medicine that cures every disease hindering the development of a nation. Keeping this view, countries put endless efforts in the development of education. Major phenomena for the development process of education include: privatization, teacher education, design of modern and well-timed course and curricula and establishment of infrastructure and logistics. For the allocation of national budget, most of the states provide the highest preference to education. Despite these efforts, many countries fail to achieve the target that is especially aimed for their national development through education. Why is this happening, since the purpose of education is to ensure national development? Encompassing of many research findings sums up that education is not playing the role according to its purpose. Thus, many prescriptions have been provided through researches with an ideology of ``Education as Right'' to solve the problems. All these suggestions are still unsuccessful to make the education system desired functional. The conducted research for this paper has to understand what would be the difference if students do not consider education as their rights, but do judge it as their assets and property. Results assert that this attitude would be able to change the psychological setup of poor students developing an ownership attitude toward education. This would irrevocably help to achieve the national goal of education. However, a new paradigm called voucherilization would be the key for the change of psychological and mental current setup of the underprivileged students.